1955
DOI: 10.1098/rspa.1955.0023
|View full text |Cite
|
Sign up to set email alerts
|

On the cubic and hexagonal close-packed lattices

Abstract: The present paper was stimulated by the discovery by Dugdale & Simon (1953) of a polymorphic transition in solid helium. A discussion is given of the relative stability of the cubic and hexagonal close-packed lattices assuming central forces of the Mie—Lennard-Jones type. Taking static lattice energy alone into account the usual laws of force favour the hexagonal close-packed lattice, the difference in energy being about 0·01%. However, lattice dynamics indicates that the equivalent Debye Θ at the absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

1963
1963
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…With his Oxford student Hugh Barron, inspired by a polymorphic fcc-to-hcp lattice transition then recently discovered in solid helium by Dugdale and Simon, he discussed the corresponding zero-point quantum-mechanical dynamics [18]. With Dugdale he later wrote an instructive review of solid helium and its phases [19] and, more generally, of the theory of melting [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With his Oxford student Hugh Barron, inspired by a polymorphic fcc-to-hcp lattice transition then recently discovered in solid helium by Dugdale and Simon, he discussed the corresponding zero-point quantum-mechanical dynamics [18]. With Dugdale he later wrote an instructive review of solid helium and its phases [19] and, more generally, of the theory of melting [20].…”
mentioning
confidence: 99%
“…First, in terms of the variable z = exp(−2J/k B T ), which vanishes when T → 0, he undertook the calculation of the exact expansion coefficients of M 0 (T ) to order z 18 . Then in 1949 [7], from an insightful analysis of the many exact coefficients and an intelligent asymptotic extrapolation, he concluded that β was close to or somewhat less than 0.16.…”
mentioning
confidence: 99%
“…If we sum over all the interactions between the atoms in a (Bravais) lattice using an ( n , m )-LJ potential, we obtain the following expression for the cohesive energy for a monatomic lattice: ,, E coh = n m italicϵ 2 ( n m ) [ L n n true( r normale R true) n L m m true( r normale R true) m ] where the so-called lattice sums L n can be defined such that the distance R reflects the nearest-neighbor distance in the crystal. The lattice sums L n contain expressions for quadratic forms or functions and depend on various cell parameters, i.e., L n ( x i ) where x i are the lattice constants (and Wyckoff positions in the case of multilattices). , Lattice sums for inverse-power potentials are related to the more general Epstein zeta function: , scriptZ ( c ; B ; u⃗ , v⃗ ) = z Z N normale 2 π normali u⃗ · B z⃗ | B...…”
Section: The Lennard-jones Potential In Solid-state Simulationsmentioning
confidence: 99%
“…Lattice Sums. If we sum over all the interactions between the atoms in a (Bravais) lattice using an (n, m)-LJ potential, we obtain the following expression for the cohesive energy for a monatomic lattice: 3,77,78…”
Section: The Lennard-jones Potential In Solid-state Simulationsmentioning
confidence: 99%
“…В роботах [102][103][104] досліджувалися деякі властивості спектру частот в зв'язку з задачами тепломісткости, стійкости ґратниці та нульової енергії. Проте, простота структури «компенсується» труднощами одержання хороших монокристалів, які б можна було досліджувати експериментально.…”
Section: методи опису енергетичного спектру електронів та спектру часunclassified